Meningkatkan Kemampuan Keaksaraan Awal Melalui Media Kartu Suku Kata Bergambar dalam Pembelajaran Blended Learning Pada Kelompok B di TK Aisyiyah Bustanul Athfal Sokawera Tahun Pelajaran 2020-2021 - Juniati Juniati (Program Studi S1 PG-PAUD, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Satya Wacana, 2023)
This study aims to improve early literacy skills through the medium of illustrated syllable cards in blanded learning in group B at Aisyiyah Bustanul Athfal Sokawera Kindergarten. this study used Classroom Action Research (CAR). The subjects of the study with the number of children as many as 15 children consisted of 8 boys and 7 girls. Data collection by observation and documentation. This study showed an improvement in each cycle. In precyclicality there were 26% of 15 children. The increase showed that in cycle 1 1st meeting showed 38%, cycle 1 2nd meeting showed an increase of 47%. In cycle 2, 1st meeting showed an increase of 71% and cycle 2, 2nd meeting showed a very disturbing success achievement of 91% so that it could exceed the predetermined achievement indicator of 80%. From the results of research that has been carried out, it shows that with the media of pictorial syllable cards, it can improve the initial literacy ability in group B aged 5-6 years.